Th1-related transcription factors and cytokines in systemic lupus erythematosus - Tang, Yang-Yang; Wang, Da-Cheng; Chen, You-Yue; Xu, Wang-Dong; Huang, An-Fang (Frontiers in Immunology, 2023)
Systemic lupus erythematosus (SLE) is an inflammatory disorder related to immunity dysfunction. The Th1 cell family including Th1 cells, transcription factor T-bet, and related cytokines IFNγ, TNFα, IL-2, IL-18, TGF-β, and IL-12 have been widely discussed in autoimmunity, such as SLE. In this review, we will comprehensively discuss the expression profile of the Th1 cell family in both SLE patients and animal models and clarify how the family members are involved in lupus development. Interestingly, T-bet-related age-associated B cells (ABCs) and low-dose IL-2 treatment in lupus were emergently discussed as well. Collection of the evidence will better understand the roles of the Th1 cell family in lupus pathogenesis, especially targeting IL-2 in lupus.